Sensitivity and Performance of Dinitroanisole (DNAN) in comparison with TNT. Issue 1 (1st August 2022) - Hussein, Ahmed K.; Elbeih, Ahmed; Abdelhafiz, Mahmoud; Ahmed, Hesham S.; Shalaby, Ahmed S. A.; Azazy, Ahmed; Saleh, Ahmed
Abstract: The constant search for protection the soldier during training and participation in hostilities led us to aspire to develop types of energetic materials of a special nature that qualify them to reach the maximum levels of safety during handling, transportation and uses. In this work, we focus on one of these compounds, which is the main component of the preparation of low sensitive compositions. DNAN is an explosive with low sensitivity. Preparation of DNAN in laboratory scale was performed; explosive characterization was presented. Impact and friction sensitivities of DNAN, heat of combustion and detonation velocity were specified. TGA and DSC were used to investigate the DNAN thermal behavior under specific conditions. It was concluded that sensitivity of DNAN is lower than TNT and the chosen cyclic nitramines. The detonation properties of DNAN are slightly lower than TNT however DNAN is candidate individually or with other explosives to replace TNT in low sensitive compositions to full fill the safety and security manipulation of ammunitions.